Cognitive network spectrum access for emergency communications - Zheng GUAN; Wen-hua QIAN; Mei-le YU (Tongxin xuebao)
A wireless cognitive network opportunistic spectrum accessing scheme which provided delay guarantee for emergency communications was proposed.Primary user (PU) and secondary users (SU) shared the spectrum resources according to the discrete time two-level exhausted and limited (k=1) polling mechanism.Then,piggyback acknowledgement was used to realize the parallel scheduling between data transportation and users access,and then reducing the time consumption cause by the user switching.Finally,the mathematics functions was set up and achieved the closed form expressions for the mean waiting time theoretical analysis and simulation experiment.It is proved that the proposed scheme is both interference restraining and high throughput with the delay guaranteed.